A Comprehensive Review of Recommender Systems in the Cultural Sector - IMAD EL-ATTAR; Lamia BENAMEUR; Mohamed CHRAYAH (Journal of Information Sciences)
One of the most essential aspects of human life is culture since it plays a crucial role in shaping their identity and worldview. The need for effective cultural recommender systems increases as globalization expands and the cultural products become more diverse. A cultural recommender system is a software tool that provides personalized recommendations for users based on their preferences and previous activity. The purpose behind such systems is to help users reach and engage with cultural content that matches their interests. Therefore, this article offers an overview of the recommender systems in the cultural sector by examining the nature of cultural products, types, benefits, applications and challenges of these systems, while testing their utility and application on three platforms: Netflix, Spotify, and Amazon.